Preparation method of wear-resistant anticorrosive coating material for repairing defects of hardware castings

By using modified phenolic resins, modified dispersants and other materials, wear-resistant and anti-corrosion coating materials are prepared, which solves the problem of insufficient wear resistance and corrosion resistance of existing coating materials, and significantly improves the repair effect and service life of hardware castings.

CN119842289AActive Publication Date: 2025-04-18JIANGSU CHENFAN IND TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510054218.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-18
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

When existing coating materials are used for repairing hardware casting defects, they have insufficient wear resistance and corrosion resistance, resulting in a short service life of repaired hardware castings and cannot meet the safety requirements in harsh environments such as high temperature, high load, and high pressure.

Method used

Wear-resistant and anti-corrosion coating materials are prepared through stirring, grinding, ultrasonic treatment and mixing processes such as modified phenolic resin, modified dispersant, composite ceramic powder, modified titanium dioxide, modified curing agent, composite defoaming agent and composite active agent.

Benefits of technology

The wear resistance, corrosion resistance, hardness and compressive strength of the repaired hardware castings are improved, the adhesion between the coating materials and the hardware castings is enhanced, the service life is extended, and safety requirements are met in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842289A_ABST
    Figure CN119842289A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of coatings, in particular to a preparation method of a wear-resistant anticorrosive coating material for hardware casting defect repair. The problem that the service life of the repaired hardware casting is short is solved. The preparation method of the wear-resistant anticorrosive coating material comprises the following steps: stirring the modified phenolic resin, the modified dispersant and other materials to obtain a first component, grinding the composite ceramic powder, the modified titanium dioxide and other materials to obtain a second component, performing ultrasonic treatment on the modified curing agent, the composite defoaming agent and other materials to obtain a third component, and preparing the wear-resistant anticorrosive coating material. And finally, mixing all the treated components and the composite active agent to obtain the wear-resistant anticorrosive coating material. According to the prepared coating material, the repaired hardware casting has excellent wear resistance and corrosion resistance, the hardness and compressive strength are high, the adhesive force between the coating material and the hardware casting is high, and the coating material has remarkable application value in hardware casting defect repairing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, in particular to a method for preparing a wear-resistant and corrosion-resistant coating material for repairing defects of hardware castings. Background Art

[0002] With the continuous development of industrial technology, metal castings are more and more widely used in various fields. In industrial production, the damage of metal castings is a common problem. Metal corrosion can cause damage to equipment, components or products and reduce their service life. Generally speaking, the damage of metal castings during their service life is caused by the formation of surface defects (such as corrosion or wear), which reduce the friction, wear and corrosion resistance of metal castings. Repairing defects through some surface treatment, coating and other methods can solve the problems that arise today. Therefore, new coating materials are gradually being used in defect repair. However, for hardware castings, there is a fatal disadvantage. The repaired hardware castings are still susceptible to wear and corrosion, resulting in failure to meet safety requirements in harsh environments such as high temperature, high load and high pressure.

[0003] Numerous experiments have proved that epoxy resin-based coating materials have excellent anti-corrosion properties and are one of the main types of anti-corrosion coatings. Epoxy resin-based coating materials have good tolerance to chemical substances such as acids, alkalis, and salts, and can protect hardware castings from corrosion in harsh chemical environments. They can effectively prevent chemical substances from corroding hardware castings and extend the service life of hardware castings. Epoxy resin-based coating materials also have excellent water resistance and are not easily penetrated and dissolved by water. They can still maintain good performance in humid or underwater environments and can prevent water from corroding and damaging hardware castings. They can also resist the influence of natural environmental factors such as ultraviolet rays and temperature changes, and are not prone to aging, fading, and powdering. They have a long service life in outdoor environments, but the wear resistance and impact resistance of epoxy resin-based coating materials after coating and curing are poor.

[0004] With the development of science and technology, many hardware castings now have defects that need to be repaired with coating materials. However, today's coating materials still have problems with poor wear resistance and corrosion resistance, resulting in a short service life of the repaired hardware castings, limiting their industrial application.

[0005] Therefore, a method for preparing a wear-resistant and anti-corrosion coating material for repairing defects in hardware castings is proposed. Summary of the invention

[0006] The purpose of the present invention is to design a preparation method of a wear-resistant and anti-corrosion coating material for repairing defects in hardware castings. The preparation method of the wear-resistant and anti-corrosion coating material in the present invention is: modified phenolic resin, modified dispersant and other materials are subjected to stirring treatment to obtain a first component, composite ceramic powder, modified titanium dioxide and other materials are subjected to grinding treatment to obtain a second component, modified curing agent, composite defoaming agent and other materials are subjected to ultrasonic treatment to obtain a third component, and finally all the treated components and composite active agent are subjected to mixing treatment to obtain a wear-resistant and anti-corrosion coating material. The coating material prepared by the present invention makes the repaired hardware castings have excellent wear resistance and corrosion resistance, and has high hardness and compressive strength. The coating material has strong adhesion to the hardware castings, and has significant application value in repairing defects in hardware castings.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing a wear-resistant and anti-corrosion coating material for repairing defects of hardware castings. The method for preparing the wear-resistant and anti-corrosion coating material comprises the following steps:

[0009] The modified phenolic resin, the first portion of epoxy resin E-51, and the modified dispersant are stirred to obtain a first component;

[0010] The composite ceramic powder, modified titanium dioxide and modified coupling agent are ground to obtain a second component;

[0011] The second portion of epoxy resin E-51, modified curing agent, and composite defoaming agent are subjected to ultrasonic treatment to obtain a third component;

[0012] The first component, the second component, the third component and the composite active agent are mixed to obtain the wear-resistant and corrosion-resistant coating material.

[0013] Preferably, the specific steps of the stirring treatment are: 17 parts of modified phenolic resin, 25 parts of the first epoxy resin E-51, 5 parts of zinc phosphate and 6 parts of modified dispersant are put into a stirring tank, stirred at a speed of 1500rpm-1900rpm and a temperature of 60℃-80℃ for 2h to obtain a first component.

[0014] Preferably, the preparation method of the modified phenolic resin is as follows: 4-6 parts of 3-fluorophenol and 25 parts of formaldehyde are put into 30 parts of toluene solution, and the solution is stirred at a pH of 10 for a pre-reaction, the stirring temperature is controlled to be 55° C., and the stirring time is 3 hours to obtain a fluorine-containing precursor; 28 parts of phenol and 3 parts of sodium hydroxide are added to the fluorine-containing precursor, and the solution is stirred for 1 hour and then transferred into a hydrothermal reactor, heated to 90° C., and reacted under autogenous pressure for 6 hours to 8 hours. After the reaction is completed, the solution is centrifuged at 8000 rpm to obtain a solid product, and the solid product is vacuum dried at 60° C. for 12 hours to obtain a modified phenolic resin.

[0015] Preferably, the preparation method of the modified dispersant is: 7 parts of sodium tripolyphosphate and 6-10 parts of triethanolamine are mixed to obtain a mixture A; 2 parts of hydrochloric acid are slowly dripped into the mixture A for 30 minutes to obtain a mixture B; 3 parts of maleic anhydride are added to the mixture B, and the mixture is transferred to a hydrothermal reactor after stirring for 30 minutes, and reacted at 120°C for 4h-6h. After the reaction is completed, the modified dispersant is obtained by centrifugal drying.

[0016] Preferably, the specific steps of the grinding treatment are: put 9 parts of composite ceramic powder, 2 parts of glass fiber, 1-3 parts of modified titanium dioxide and 3 parts of modified coupling agent into a ball mill, use deionized water as the medium, grind for 10min-30min, and the particle size is 30μm-50μm to obtain the second component; the composite ceramic powder is composed of silicon carbide and aluminum oxide, and the weight ratio of the silicon carbide to the aluminum oxide is 1:1-3.

[0017] Preferably, the preparation method of modified titanium dioxide is: slowly adding 8 parts of tetrabutyl titanate to 10 parts of anhydrous ethanol, stirring evenly to form solution A; dissolving 1 part of chromium nitrate in 5 parts of deionized water to form solution B; under stirring conditions, slowly dropping the solution B into the solution A, adding 0.5 parts of glacial acetic acid as an inhibitor, and continuing to stir for 2 hours to form a uniform sol; standing the sol at 60°C to allow it to undergo a gelation process to form a wet gel; drying the wet gel at 40°C to remove the solvent and moisture therein to obtain a dry gel; then calcining the dry gel in a muffle furnace, calcining at 450°C-550°C for 2 hours under a nitrogen atmosphere, and a heating rate of 10°C / min to obtain modified titanium dioxide.

[0018] Preferably, the preparation method of the modified coupling agent is: dissolving 20 parts of γ-aminopropyltriethoxysilane in 10 parts of toluene to obtain solution C; dissolving 12 parts of epoxy resin E-44 and 0.5 parts of glacial acetic acid in 10 parts of toluene to obtain solution D; slowly adding the solution D dropwise to the solution C, then stirring at 60°C-76°C for 90min-130min, washing with ethanol after the reaction is completed and drying in a vacuum drying oven at 60°C for 12h to obtain the modified coupling agent.

[0019] Preferably, the specific steps of ultrasonic treatment are: putting the second portion of epoxy resin, modified curing agent and composite defoamer into a beaker and then putting it into an ultrasonic machine, ultrasonicating at 70°C-90°C for 5 hours at a power of 120W to obtain a third component; the composite defoamer is a mixture of DF-455 and SH-201, and the weight ratio of DF-455 to SH-201 is 2-4:3.

[0020] Preferably, the preparation method of the modified curing agent is: under nitrogen protection, 6 parts of toluene diisocyanate are added to a reaction container, the temperature is stirred and raised to 40°C, 2 parts of butyl acetate solution are added dropwise, the temperature is controlled between 40°C-80°C, and the reaction is kept warm for 6 hours. When the -NCO content is 8.1%-8.5%, 1 part of benzoyl chloride is added to terminate the reaction, and the modified curing agent is obtained by centrifugation.

[0021] Preferably, the specific steps of the mixing treatment are: putting the first component, the second component, the third component and the composite active agent into a mixer, mixing for 11min-15min at a rotation speed of 850rpm-1050rpm at 150°C to obtain a wear-resistant and anti-corrosion coating material; the composite active agent is a mixture of ethylenediamine, stearic acid and n-dodecyl mercaptan, and the weight ratio of the ethylenediamine, the stearic acid and the n-dodecyl mercaptan is 2:1:1-3.

[0022] Preferably, the wear-resistant and anti-corrosion coating material is used in the repair of defects in hardware castings.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. The present invention uses the first epoxy resin E-51 as the matrix material in the first component, adds modified phenolic resin and modified dispersant and stirs to improve the anti-corrosion performance of the repaired hardware castings. The phenolic resin is fluorine-modified to obtain a modified phenolic resin, which has good chemical stability and can form a dense protective film on the surface of the hardware castings to prevent chemical substances such as acids, alkalis, and salts from contacting the hardware castings, thereby extending the service life of the hardware castings in harsh chemical environments; sodium tripolyphosphate and triethanolamine are acid-base modified, and the obtained modified dispersant can make the material evenly dispersed, make the coating material more dense, and effectively prevent corrosive media such as water, oxygen, and ions from penetrating into the surface of the hardware castings, thereby improving the corrosion resistance of the hardware castings and extending the service life of the hardware castings; the modified phenolic resin and the modified dispersant can synergistically form a dense film on the surface of the hardware castings, thereby improving its corrosion resistance, and the corrosion depth is only 18.7μm.

[0025] 2. The present invention adds composite ceramic powder and modified titanium dioxide to the second component for grinding treatment. The two materials can work together to improve the impact strength of the repaired hardware castings. After the composite ceramic powder is combined with the hardware castings, its overall strength can be enhanced. When subjected to external force impact, the ceramic phase can absorb and disperse energy, improve the impact resistance of the hardware castings, prevent the coating material from breaking or falling off, and enable the hardware castings to maintain good performance when subjected to dynamic loads or impact loads; the modified titanium dioxide prepared by chromium-doped titanium dioxide has higher strength, and can be evenly dispersed in the coating material to play a reinforcing role, improve the impact strength of the coating material, and extend the service life of the hardware castings; the composite ceramic powder can fill the larger pores in the coating material, while the modified titanium dioxide has a smaller particle size and can fill the tiny gaps between the coating materials. The two cooperate with each other to make the coating material more dense and improve the impact strength of the repaired hardware castings. The final impact strength is 94Kg.cm.

[0026] 3. In the third component of the present invention, the second epoxy resin E-51 is used as the matrix material, and a modified curing agent and a composite defoaming agent are added for ultrasonic treatment to improve the hardness of the repaired hardware casting. After the composite defoaming agent eliminates bubbles, the pores and defects in the coating material are reduced, and the modified curing agent prepared by modifying the epoxy group can promote the epoxy resin and other components in the coating material to fully crosslink and solidify, forming a more compact three-dimensional network structure. This synergistic effect greatly improves the density of the coating material; after the composite defoaming agent eliminates bubbles, the damage to the structure by bubbles is avoided, making the coating material repaired on the hardware casting more uniform and complete, so that the mechanical properties given by the modified curing agent can be better exerted, so that the hardness of the repaired hardware casting is improved, and the Vickers hardness is 986HV.

[0027] 4. The present invention adds a modified coupling agent to the second component, and this material can make the combination between the first component, the second component and the third component more tightly, thereby improving the adhesion of the coating material and the hardware casting. The modified coupling agent molecule prepared by trimerization reaction modification of toluene diisocyanate can react chemically with the hydroxyl group on the surface of the modified titanium dioxide at one end, and can react cross-linkingly with the epoxy resin in the coating material at the other end, thereby tightly combining the hardware casting and the coating material, greatly improving the adhesion of the coating material, and making it less likely to fall off on the surface of the hardware casting; the surface of the hardware casting can also be activated to increase the roughness and active sites of the surface of the hardware casting, so that the coating material can better contact and combine with the surface of the hardware casting, further enhancing the adhesion, and the bonding strength is 56.7MPa.

[0028] 5. The present invention adds a composite active agent during the mixing process of the first component, the second component, and the third component, thereby improving the wear resistance of the repaired hardware casting. The composite active agent can promote the formation of a denser and more stable passivation film on the surface of the hardware casting, participate in the curing reaction of the coating material, promote the formation of a more complete cross-linked network structure inside the coating material, and improve the hardness of the coating, thereby improving its wear resistance; putting all the treated components into a mixer for heating and mixing can effectively disperse the components and make the components with different functions fully contact and interact with each other, thereby better exerting the synergistic effect between them, and the final wear loss is 0.48 mg / h. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a flow chart of the preparation method of the present invention.

[0030] Figure 2 It is a wear amount diagram of Example 37, Examples 40-45 and Comparative Examples 17-20 of the present invention. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Specific reference Figure 1 to Figure 2 The present invention provides a method for preparing a wear-resistant and anti-corrosion coating material for repairing defects in hardware castings. The technical scheme is as follows:

[0033] The substance information involved in the present invention is as follows:

[0034] DF-455: purchased from Dongguan Defeng Defoamer Co., Ltd.; SH-201: purchased from Hubei Longsheng Sihai New Materials Co., Ltd.

[0035] Example 1

[0036] Preparation of modified phenolic resin:

[0037] Put 4 parts of 3-fluorophenol and 25 parts of formaldehyde into 30 parts of toluene solution, stir for pre-reaction at pH 10, control the stirring temperature to 55°C, and stir for 3 hours to obtain a fluorine-containing precursor; add 28 parts of phenol and 3 parts of sodium hydroxide to the fluorine-containing precursor, stir for 1 hour, then transfer into a hydrothermal reactor, heat to 90°C, react under autogenous pressure for 6 hours, centrifuge at 8000 rpm after the reaction to obtain a solid product, and vacuum dry the solid product at 60°C for 12 hours to obtain a modified phenolic resin.

[0038] Preparation of modified dispersant:

[0039] Mix 7 parts of sodium tripolyphosphate and 6 parts of triethanolamine to obtain mixture A; slowly drip 2 parts of hydrochloric acid into the mixture A for 30 minutes to obtain mixture B; add 3 parts of maleic anhydride to the mixture B, stir for 30 minutes and then transfer to a hydrothermal reactor, react at 120°C for 4 hours, and centrifuge and dry after the reaction to obtain a modified dispersant.

[0040] Preparation of modified titanium dioxide:

[0041] 8 parts of tetrabutyl titanate are slowly added to 10 parts of anhydrous ethanol, and stirred evenly to form solution A; 1 part of chromium nitrate is dissolved in 5 parts of deionized water to form solution B; under stirring conditions, the solution B is slowly dropped into the solution A, and 0.5 parts of glacial acetic acid is added as an inhibitor, and stirring is continued for 2 hours to form a uniform sol; the sol is allowed to stand at 60°C to allow it to undergo a gelation process to form a wet gel; the wet gel is dried at 40°C to remove the solvent and moisture therein to obtain a dry gel; the dry gel is then calcined in a muffle furnace at 450°C for 2 hours under a nitrogen atmosphere with a heating rate of 10°C / min to obtain modified titanium dioxide.

[0042] Preparation of modified coupling agent:

[0043] 20 parts of γ-aminopropyltriethoxysilane were dissolved in 10 parts of toluene to obtain solution C; 12 parts of epoxy resin E-44 and 0.5 parts of glacial acetic acid were dissolved in 10 parts of toluene to obtain solution D; the solution D was slowly added dropwise to the solution C, followed by stirring at 60°C for 90 minutes. After the reaction was completed, the solution was washed with ethanol and dried in a vacuum drying oven at 60°C for 12 hours to obtain a modified coupling agent.

[0044] Preparation of modified curing agent:

[0045] Under nitrogen protection, add 6 parts of toluene diisocyanate to the reaction container, stir and heat to 40°C, add 2 parts of butyl acetate solution dropwise, control the temperature at 40°C, and keep the reaction for 6 hours. When the -NCO content is 8.1%, add 1 part of benzoyl chloride to terminate the reaction, and centrifuge to obtain a modified curing agent.

[0046] Preparation of wear-resistant and anti-corrosion coating materials:

[0047] 17 parts of modified phenolic resin, 25 parts of the first epoxy resin E-51, 5 parts of zinc phosphate and 6 parts of modified dispersant were put into a stirring kettle, and stirred at a speed of 1500 rpm and a temperature of 60° C. for 2 hours to obtain a first component;

[0048] 9 parts of composite ceramic powder, 2 parts of glass fiber, 1 part of modified titanium dioxide and 3 parts of modified coupling agent are put into a ball mill, and deionized water is used as a medium, and the mixture is ground for 10 minutes, and the particle size is 30 μm, to obtain a second component; the composite ceramic powder is composed of silicon carbide and aluminum oxide, and the weight ratio of the silicon carbide to the aluminum oxide is 1:1;

[0049] Put the second portion of epoxy resin, modified curing agent and composite defoamer into a beaker and then into an ultrasonic machine, and ultrasonicate at 70°C for 5 hours at a power of 120 W to obtain a third component; the composite defoamer is a mixture of DF-455 and SH-201, and the weight ratio of DF-455 to SH-201 is 2:3;

[0050] The first component, the second component, the third component and the composite active agent are put into a mixer, and mixed at 150°C and 850rpm for 11 minutes to obtain a wear-resistant and anti-corrosion coating material; the composite active agent is a mixture of ethylenediamine, stearic acid and n-dodecyl mercaptan, and the weight ratio of the ethylenediamine, the stearic acid and the n-dodecyl mercaptan is 2:1:1.

[0051] Example 2-13

[0052] Referring to the parameter conditions of the preparation method in Example 1, the specific differences are shown in Table 1.

[0053] Table 1 Parameter conditions of Examples 1-13

[0054]

[0055] Comparative Example 1 refers to the parameter conditions of the preparation method in Example 1, except that no modified phenolic resin is added.

[0056] Comparative Example 2 refers to the parameter conditions of the preparation method in Example 1, except that 3-fluorophenol is not added to the synthetic phenolic resin.

[0057] Comparative Example 3 refers to the parameter conditions of the preparation method in Example 1, except that no modified dispersant is added.

[0058] Comparative Example 4 refers to the parameter conditions of the preparation method in Example 1, except that the triethanolamine is not modified.

[0059] Example 14 Anticorrosion Ability

[0060] According to the standard GB / T 7998-2005, an intergranular corrosion test (IGC) was performed to test the final corrosion depth of Examples 1-13 and Comparative Examples 1-4. The results are shown in Table 2.

[0061] Table 2 Anticorrosion ability of Examples 1-13 and Comparative Examples 1-4

[0062] Example Corrosion depth / μm Example 1 35.4 Example 2 32.6 Example 3 34.9 Example 4 29.2 Example 5 31.5 Example 6 26.7 Example 7 28.5 Example 8 24.1 Example 9 26.5 Example 10 21.6 Embodiment 11 23.4 Example 12 18.7 Example 13 21.3 Comparative Example 1 61.7 Comparative Example 2 54.3 Comparative Example 3 59.6 Comparative Example 4 51.2

[0063] It can be found from Table 2 that in Comparative Examples 1-2, if the modified phenolic resin is not added, the anti-corrosion performance of the repaired hardware casting is the worst, and only by adding phenolic resin, although the anti-corrosion performance is improved, the corrosion is still very deep, indicating that the addition of modified phenolic resin can promote the improvement of the anti-corrosion performance of the coating material; in Comparative Examples 3-4, no modified dispersant is added or triethanolamine is not modified, and the anti-corrosion performance of the repaired hardware casting is poorer than that of the embodiment, which indicates that the modified dispersant plays an important role in the first component. If it is not added, it will cause agglomeration between the components, thereby affecting the reaction between the materials, thereby reducing the anti-corrosion performance of the repaired hardware casting. In Examples 1-5, some parameters in the synthetic modified phenolic resin were changed, and the anti-corrosion performance of Example 4 was the best, with a corrosion depth of 29.2 μm, because the modified phenolic resin has good chemical stability and can form a dense protective film on the surface of the hardware castings, preventing chemicals such as acids, alkalis, and salts from contacting the hardware castings, and extending the service life of the hardware castings in harsh chemical environments; in Examples 6-9, some preparation parameters in the synthetic modified dispersant were changed, and the anti-corrosion performance of the repaired hardware castings was the best when the amount of triethanolamine was 8 parts and the reaction time was 5 hours, and the corrosion depth of Example 8 was only 24.1 μm, which is because the modified dispersant can make the material Uniform dispersion makes the coating material more compact, which can effectively prevent corrosive media such as water, oxygen, and ions from penetrating into the surface of hardware castings, improve the corrosion resistance of hardware castings, and extend the service life of hardware castings; in Examples 10-13, the parameter conditions in the stirring treatment are changed, and Example 12 has the best anti-corrosion performance and the smallest corrosion depth of 18.7 μm, because the stirring treatment can make the modified phenolic resin, modified dispersant and epoxy resin fully contact and interpenetrate with each other to form a uniform multi-component system, and the modified phenolic resin and modified dispersant can synergistically form a dense film on the surface of the hardware casting, thereby improving its corrosion resistance and extending the service life of the hardware casting.

[0064] Examples 15-24

[0065] Referring to the parameter conditions of the preparation method in Example 12, the difference is that the preparation parameters of the composite ceramic powder and modified titanium dioxide and the process parameters of the grinding treatment are changed, as shown in Table 3.

[0066] Table 3 Parameter conditions of Example 12 and Examples 15-24

[0067]

[0068] Comparative Example 5 refers to the parameter conditions of the preparation method in Example 12, except that no composite ceramic powder is added.

[0069] Comparative Example 6 refers to the parameter conditions of the preparation method in Example 12, except that only silicon carbide is added.

[0070] Comparative Example 7 refers to the parameter conditions of the preparation method in Example 12, except that only aluminum oxide is added.

[0071] Comparative Example 8 refers to the parameter conditions of the preparation method in Example 12, except that no modified titanium dioxide is added.

[0072] Comparative Example 9 refers to the parameter conditions of the preparation method in Example 12, except that only titanium dioxide is added.

[0073] Example 25 Impact strength test

[0074] Fix Example 12, Examples 15-24 and Comparative Examples 5-9 on a fixture, select a weight of appropriate mass and a drop height according to the coating material properties and the expected impact strength, release the weight to allow it to fall freely to impact the repaired surface, observe and record, and the results are shown in Table 4.

[0075] Table 4 Impact strength test of Example 12, Examples 15-24 and Comparative Examples 5-9

[0076] Example Impact strength / Kg.cm Example 12 75 Embodiment 15 79 Example 16 76 Embodiment 17 83 Embodiment 18 80 Embodiment 19 86 Embodiment 20 82 Embodiment 21 90 Embodiment 22 88 Embodiment 23 94 Embodiment 24 91 Comparative Example 5 56 Comparative Example 6 61 Comparative Example 7 62 Comparative Example 8 59 Comparative Example 9 66

[0077] It can be found from Table 4 that in Comparative Examples 5-7, when the composite ceramic powder is not added, the impact resistance of the repaired hardware castings is poor, which will shorten their service life. When only one ceramic powder is added, although the impact resistance is improved, it is still lower than that of the comparative embodiment, because the single ceramic powder cannot provide sufficient strength to withstand the impact, so that the impact resistance of the repaired hardware castings is reduced; in Comparative Examples 8-9, no modified titanium dioxide is added or unmodified titanium dioxide is added, and the impact resistance of the repaired hardware castings is also significantly reduced, indicating that the presence of modified titanium dioxide can promote the improvement of impact resistance. In Example 12 and Examples 15-20, the preparation parameters of the composite ceramic powder and the modified titanium dioxide were changed, and the performance of Example 19 was the best, which was 86Kg.cm. This is because after the composite ceramic powder is combined with the hardware casting, its overall strength can be enhanced. When subjected to external impact, the ceramic phase can absorb and disperse energy, improve the impact resistance of the hardware casting, prevent the coating material from cracking or falling off, and enable the hardware casting to maintain good performance when subjected to dynamic loads or impact loads. The modified titanium dioxide has a higher strength and can be evenly dispersed in the coating material to play a reinforcing role, improve the impact strength of the coating material, and extend the life of the hardware casting. Service life; In Examples 21-24, the parameters of the grinding treatment are controlled, among which Example 23 has the best impact resistance, which is 94Kg.cm, because through the grinding treatment, larger particles can be refined to make the particle size distribution more uniform, which helps to achieve more uniform dispersion in the coating material, thereby improving the performance of the coating material; the composite ceramic powder can fill the larger pores in the coating material, and the modified titanium dioxide has a smaller particle size and can fill the tiny gaps between the coating materials. The two cooperate with each other to make the coating material denser, improve the impact resistance of the repaired hardware castings, and extend the service life of the repaired hardware castings.

[0078] Examples 26-33

[0079] Referring to the parameter conditions of the preparation method in Example 23, the difference is that the preparation parameters of the modified curing agent and the composite defoaming agent and the process parameters of the ultrasonic treatment are changed, as shown in Table 5.

[0080] Table 5 Parameter conditions of Example 23 and Examples 26-33

[0081]

[0082] Comparative Example 10 refers to the parameter conditions of the preparation method in Example 23, except that no modified curing agent is added.

[0083] Comparative Example 11 refers to the parameter conditions of the preparation method in Example 23, except that only toluene diisocyanate is added as a curing agent.

[0084] Comparative Example 12 refers to the parameter conditions of the preparation method in Example 23, except that no composite defoaming agent is added.

[0085] Comparative Example 13 refers to the parameter conditions of the preparation method in Example 23, except that only DF-455 is added.

[0086] Comparative Example 14 refers to the parameter conditions of the preparation method in Example 23, except that only SH-201 is added.

[0087] Example 34 Vickers Hardness Test

[0088] The Vickers hardness of Example 23, Examples 26-33 and Comparative Examples 10-14 was tested by Vickers hardness test, and the results are shown in Table 6.

[0089] Table 6 Vickers hardness test of Example 23, Examples 26-33 and Comparative Examples 10-14

[0090] Example Vickers hardness / HV Embodiment 23 872 Embodiment 26 893 Embodiment 27 877 Embodiment 28 929 Embodiment 29 902 Embodiment 30 958 Embodiment 31 936 Embodiment 32 986 Embodiment 33 961 Comparative Example 10 756 Comparative Example 11 813 Comparative Example 12 784 Comparative Example 13 845 Comparative Example 14 836

[0091] It can be found from Table 6 that in Comparative Examples 10-11, when no modified curing agent is added or only toluene diisocyanate is added as a curing agent, it can be found that the hardness of the repaired hardware casting is not high, which shows that the modified curing agent can significantly improve the performance of the coating material, and the modification of toluene diisocyanate can improve its curing performance; in Comparative Examples 12-14, when no composite defoaming agent is added or only one defoaming agent is added, the hardness of the repaired hardware casting is still lower than that of the embodiment, indicating that the composite defoaming agent plays a more significant role in the coating material. In Example 23 and Examples 26-29, the parameter conditions of the synthetic modified curing agent are controlled. At this time, the hardness of Example 28 is the highest, which is 929HV. This is because the modified curing agent can make the curing reaction more complete, increase the cross-linking density of the coating material, and form a more complete three-dimensional network structure, thereby improving the hardness of the repaired hardware castings; in Examples 30-31, the weight ratio of DF-455 and SH-201 is changed, and the hardness of Example 30 is 958HV. Because the performance of a single defoaming agent is poor, the composite defoaming agent can eliminate internal bubbles before the coating material is cured, so that the coating material forms a uniform and dense structure, thereby improving the hardness of the repaired hardware castings; in Examples 32-33, controlling the temperature of the ultrasonic treatment can provide more energy for the molecules involved in the synthesis reaction, make the molecular motion more intense, increase the collision frequency and effective collision probability between molecules, thereby accelerating the chemical reaction rate. At this time, the Vickers hardness of Example 32 is 986HV. After the composite defoamer eliminates the bubbles, the pores and defects in the coating material are reduced, and the modified curing agent can promote the epoxy resin and other components in the coating material to fully cross-link and cure to form a denser three-dimensional network structure. This synergistic effect greatly improves the density of the coating material; and after the bubbles are eliminated, the damage to the structure by the bubbles is avoided, making the coating material repaired on the hardware casting more uniform and complete, so that the mechanical properties given by the modified curing agent can be better exerted, and the hardness of the repaired hardware casting is improved.

[0092] Examples 35-38

[0093] Referring to the parameter conditions of the preparation method in Example 32, the difference is that the preparation parameters of the modified coupling agent are changed, as shown in Table 7.

[0094] Comparative Example 15 refers to the parameter conditions of the preparation method in Example 32, except that no modified coupling agent is added.

[0095] Comparative Example 16 refers to the parameter conditions of the preparation method in Example 32, except that only γ-aminopropyltriethoxysilane is added as a coupling agent.

[0096] Example 39 Adhesion Test

[0097] The bonding strength of Example 32, Examples 35-38 and Comparative Examples 15-16 was tested by a pull-off test, and the results are shown in Table 7.

[0098] Table 7 Adhesion test of Example 32, Examples 35-38 and Comparative Examples 15-16

[0099]

[0100] It can be found from Table 7 that in Example 32, Examples 35-38 and Comparative Examples 15-16, the coating material has poor adhesion and is easy to fall off after repair, thereby affecting the service life of the repaired hardware castings. However, the modified coupling agent is added, which can make the combination between the first component, the second component and the third component more closely, thereby improving the adhesion of the coating material and the hardware castings, and one end of the modified coupling agent molecule can be bonded to the hydroxyl group on the surface of the modified titanium dioxide. A chemical reaction occurs, and the other end can undergo a cross-linking reaction with the epoxy resin in the coating material, thereby tightly combining the hardware casting and the coating material together, greatly improving the adhesion of the coating material, and making it less likely to fall off the surface of the hardware casting; the surface of the hardware casting can also be activated to increase the roughness and active sites of the surface of the hardware casting, so that the coating material can better contact and combine with the surface of the hardware casting, further enhancing the adhesion. The bonding strength of Example 37 is 56.7MPa, which extends the service life of the repaired hardware casting.

[0101] Examples 40-45

[0102] Referring to the parameter conditions of the preparation method in Example 37, the difference is that the preparation parameters of the composite active agent and the process parameters of the mixing treatment are changed, as shown in Table 8.

[0103] Comparative Example 17 refers to the parameter conditions of the preparation method in Example 37, except that no composite active agent is added.

[0104] Comparative Example 18 refers to the parameter conditions of the preparation method in Example 37, except that only n-dodecyl mercaptan is added.

[0105] Comparative Example 19 refers to the parameter conditions of the preparation method in Example 37, except that only ethylenediamine is added.

[0106] Comparative Example 20 refers to the parameter conditions of the preparation method in Example 37, except that only stearic acid is added.

[0107] Example 46 Wear Test

[0108] Example 37, Examples 40-45 and Comparative Examples 17-20 were subjected to wear tests, and the mass changes before and after wear were measured to calculate the wear rate. The results are shown in Table 8 and Figure 2 shown.

[0109] Table 8 Wear test of Example 37, Examples 40-45 and Comparative Examples 17-20

[0110]

[0111]

[0112] From Table 8 and Figure 2 It can be found that in Comparative Examples 17-20, Example 37 and Example 40-41, no composite active agent is added or only a single active agent is added, and the wear resistance of the repaired hardware casting is poor, and the problem of short life still exists; when the composite active agent is added, its presence can promote the formation of a denser and more stable passivation film on the surface of the hardware casting, and participate in the curing reaction of the coating material with the modified curing agent, promote the formation of a more perfect cross-linked network structure inside the coating material, and improve the hardness of the coating, thereby improving its wear resistance. In Example 42-45, the rotation speed and time of the mixing treatment are controlled, and the wear resistance of Example 44 is the best, and the wear amount is only 0.48 mg / h. This is because all the components after treatment are placed in a mixer for heating and mixing. When the rotation speed is moderate, the reactants can fully contact, the reaction rate is accelerated, and it is beneficial to improve the synthesis efficiency; the mixing time is too short, the components are not fully mixed in time, and the expected uniformity cannot be achieved. As the mixing time is extended, the components have more time to diffuse, penetrate and evenly distribute with each other, and the mixing effect is gradually improved, so as to better play the synergistic effect between them.

[0113] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a wear-resistant and anti-corrosion coating material for repairing defects in hardware castings, characterized in that: The preparation method of the wear-resistant and anti-corrosion coating material comprises the following steps: The modified phenolic resin, the first portion of epoxy resin E-51, and the modified dispersant are stirred to obtain a first component; The composite ceramic powder, modified titanium dioxide and modified coupling agent are ground to obtain a second component; The second portion of epoxy resin E-51, modified curing agent, and composite defoaming agent are subjected to ultrasonic treatment to obtain a third component; The first component, the second component, the third component and the composite active agent are mixed to obtain the wear-resistant and anti-corrosion coating material.

2. The method for preparing the wear-resistant and anti-corrosion coating material for repairing defects of hardware castings according to claim 1, characterized in that: The specific steps of the stirring treatment are: put 17 parts of the modified phenolic resin, 25 parts of the first epoxy resin E-51, 5 parts of zinc phosphate and 6 parts of the modified dispersant into a stirring kettle, stir for 2 hours at a speed of 1500rpm-1900rpm and a temperature of 60℃-80℃ to obtain the first component.

3. The method for preparing the wear-resistant and anti-corrosion coating material for repairing defects of hardware castings according to claim 1, characterized in that: The preparation method of the modified phenolic resin is as follows: 4-6 parts of 3-fluorophenol and 25 parts of formaldehyde are put into 30 parts of toluene solution, and the solution is stirred at a pH of 10 for pre-reaction, and the stirring temperature is controlled to be 55° C. and the stirring time is 3 hours to obtain a fluorine-containing precursor; 28 parts of phenol and 3 parts of sodium hydroxide are added to the fluorine-containing precursor, and the solution is stirred for 1 hour and then transferred into a hydrothermal reactor, heated to 90° C., and reacted under autogenous pressure for 6 hours to 8 hours. After the reaction is completed, the solution is centrifuged at 8000 rpm to obtain a solid product, and the solid product is vacuum dried at 60° C. for 12 hours to obtain the modified phenolic resin.

4. The method for preparing the wear-resistant and anti-corrosion coating material for repairing defects of hardware castings according to claim 1, characterized in that: The preparation method of the modified dispersant is as follows: 7 parts of sodium tripolyphosphate and 6-10 parts of triethanolamine are mixed to obtain a mixture A; 2 parts of hydrochloric acid are slowly dripped into the mixture A for 30 minutes to obtain a mixture B; 3 parts of maleic anhydride are added to the mixture B, and the mixture is transferred to a hydrothermal reactor after stirring for 30 minutes, reacted at 120° C. for 4 hours to 6 hours, and centrifugally dried after the reaction to obtain the modified dispersant.

5. The method for preparing the wear-resistant and anti-corrosion coating material for repairing defects of hardware castings according to claim 1, characterized in that: The specific steps of the grinding treatment are: put 9 parts of the composite ceramic powder, 2 parts of glass fiber, 1-3 parts of the modified titanium dioxide and 3 parts of the modified coupling agent into a ball mill, use deionized water as the medium, grind for 10min-30min, and the particle size is 30μm-50μm to obtain the second component; the composite ceramic powder is composed of silicon carbide and aluminum oxide, and the weight ratio of the silicon carbide to the aluminum oxide is 1:1-3.

6. The method for preparing the wear-resistant and anti-corrosion coating material for repairing defects of hardware castings according to claim 1, characterized in that: The preparation method of the modified titanium dioxide is as follows: 8 parts of tetrabutyl titanate are slowly added into 10 parts of anhydrous ethanol, and stirred to form a solution A; Dissolve 1 part of chromium nitrate in 5 parts of deionized water to form solution B; slowly drop the solution B into the solution A under stirring conditions, add 0.5 parts of glacial acetic acid as an inhibitor, and continue stirring for 2 hours to form a uniform sol; let the sol stand at 60°C to allow it to undergo a gelation process to form a wet gel; dry the wet gel at 40°C to remove the solvent and moisture therein to obtain a dry gel; then calcine the dry gel in a muffle furnace at 450°C-550°C for 2 hours under a nitrogen atmosphere with a heating rate of 10°C / min to obtain the modified titanium dioxide.

7. The method for preparing the wear-resistant and anti-corrosion coating material for repairing defects of hardware castings according to claim 1, characterized in that: The preparation method of the modified coupling agent is as follows: dissolving 20 parts of γ-aminopropyltriethoxysilane in 10 parts of toluene to obtain solution C; dissolving 12 parts of epoxy resin E-44 and 0.5 parts of glacial acetic acid in 10 parts of toluene to obtain solution D; slowly dropping the solution D into the solution C, then stirring at 60°C-76°C for 90min-130min, washing with ethanol after the reaction is completed and drying in a vacuum drying oven at 60°C for 12h to obtain the modified coupling agent.

8. The method for preparing the wear-resistant and anti-corrosion coating material for repairing defects of hardware castings according to claim 1, characterized in that: The specific steps of the ultrasonic treatment are: putting the second epoxy resin, the modified curing agent and the composite defoamer into a beaker and then putting them into an ultrasonic machine, ultrasonicating at 70°C-90°C for 5 hours at a power of 120W to obtain the third component; the composite defoamer is a mixture of DF-455 and SH-201, and the weight ratio of DF-455 to SH-201 is 2-4:

3.

9. The method for preparing the wear-resistant and anti-corrosion coating material for repairing defects of hardware castings according to claim 1, characterized in that: The preparation method of the modified curing agent is as follows: under nitrogen protection, 6 parts of toluene diisocyanate are added to a reaction container, the temperature is raised to 40°C with stirring, 2 parts of butyl acetate solution are added dropwise, the temperature is controlled between 40°C and 80°C, the reaction is kept warm for 6 hours, when the -NCO content is 8.1%-8.5%, 1 part of benzoyl chloride is added to terminate the reaction, and the modified curing agent is obtained by centrifugation.

10. The method for preparing the wear-resistant and anti-corrosion coating material for repairing defects of hardware castings according to claim 1, characterized in that: The specific steps of the mixing treatment are: putting the first component, the second component, the third component and the composite active agent into a mixer, mixing for 11min-15min at a speed of 850rpm-1050rpm at 150°C to obtain the wear-resistant and anti-corrosion coating material; the composite active agent is a mixture of ethylenediamine, stearic acid and n-dodecyl mercaptan, and the weight ratio of the ethylenediamine, the stearic acid and the n-dodecyl mercaptan is 2:1:1-3.

Citation Information

Patent Citations

  • Chromium-silver co-doped nano TiO2 photo-catalyst, and preparation method and use thereof

    CN103861593A

  • Method for preparing epoxy novolac nanometer anticorrosive paint

    CN105219208A

  • Oligomer containing fluorine and phthalonitrile, condensate and preparation method thereof

    CN107266336A

  • High-adhesive-force anti-corrosion epoxy coating as well as preparation method and use method thereof

    CN117757333A